Determining the Market for Marine Wildlife Tourism in South Africa. - Dr L Geldenhuys; Prof P van der Merwe; M Saayman (PhD) (African Journal of Hospitality, Tourism and Leisure, 2019)
Viewing and interacting with wildlife in their natural habitat has become an important component of the tourism industry. Shark cage diving and whale watching are two prominent activities in South Africa and are becoming an increasingly popular tourist attraction. Humans are fascinated with these animals and want to have a closeup experience. The literature clearly indicates an increase in the interest of tourists towards marine wildlife activities. The behaviour of these participants, referring specifically to the profile, reasons for participation, and experiences when participating in marine wildlife activities, needs clarification. If these behaviours are known, marketing can be done more effectively. Gaining an understanding of why these participants join in marine wildlife activities, the industry can hopefully be managed more effectively and efficiently. Therefore, the purpose of this research is to determine the market of marine wildlife tourists in terms of shark cage diving and whale watching. Quantitative, descriptive methods are employed in the form of a survey, where questionnaires were administered to participants of shark cage diving and whale watching. The profile of these tourists is indicative of mostly international participants who have never participated in similar activities before, between the ages of 35 and 40 years. The motives of tourists to participate indicate that an experience, being educated about marine wildlife, the feeling of success gained through the activity and being close to marine wildlife are all important motivations for certain tourists. Six market segments have been identified, namely thrill seekers, thalassophiles (from the Greek ‘friends of the sea’), risk takers, adrenaline seekers, consorts and experience seekers (T2RACE). The results obtained from this research are hopefully going to be very useful for improving the understanding of the marine wildlife tourism market, development of marine wildlife tourism participation guidelines, and in enhancing quality of offerings and best practices.